Teacher’s Attitudes Towards the Effects of Lesson Plan on Classroom Management: A Case Study of Sufi Sahab Zakur High School - Moradi, Mehdi (American International Journal of Social Science Research, 2019)
The present study has been conducted to investigate the teacher’s attitudes towards the effects of lesson plan. Furthermore, the second goal of the study is to investigate the effects of lesson plan on classroom management. Similarly, the questionnaire had two parts the first part had 6 items and the second part had 6 items too and applied randomly. Besides, the data analyzing was performed in SPSS (version, 21) and bring out the mean and standard division. Finally, the findings reveled the importance and role of lesson planning on classroom management numbered as follow: (1) Planning is the most appropriate skill that the teacher needs to create a successful one. (2) The effective teacher is the one who plan effective lessons. (3) Preparation is the most important thing a teacher does. In addition, the following factors are related to the effects of lesson plan on classroom management. (1) Planning is a necessary skill to develop an organized learning environment. (2) Good planning minimizes class management problems. (3) A successful learning environment is the result of well lesson plan.